MONITORING OF HEART RATE VARIABILITY IN OPERATIONAL LEVEL OFFICERS DURING THE PERIOD OF MARTIAL LAW (Physical Culture and Sport: Scientific Perspective, 2025)
This study investigates heart rate variability (HRV) parameters in operational level officers serving under martial law conditions, aiming to assess their adaptive physiological responses to sustained psycho-emotional and physical stressors. Given the uniquely demanding nature of military operations during martial law, objective evaluation of autonomic nervous system regulation is critical for understanding officers’ functional state and resilience.The research sample comprised 279 male military personnel aged 30 to 52 years, actively engaged in operational command roles. Both time-domain and frequency-domain HRV metrics were analyzed, including stress index, total spectral power (TP), low-frequency (LF), and high-frequency (HF) components, which respectively reflect sympathetic and parasympathetic autonomic influences.Median heart rate was 73.4 beats per minute with a coefficient of variation of 54.2 %, indicating significant inter-individual variability and population heterogeneity. The median RRNN interval was 820.3 ms (interquartile range: 734.7–901.9 ms), consistent with moderate sympathetic activation typical of sustained alertness. High variability in RMSSD (V= 83. 1%) and pNN50 (V=136.9 %) further reflected diverse autonomic adjustments to chronic operational stress.The median total spectral power reached 964.5 ms² with an interquartile range from 636.0 to 1749.0 ms², which suggests a moderate level of autonomic regulation overall, accompanied by notable individual differences. The very low-frequency component demonstrated marked variability, with a median value of 418.5 ms² and a coefficient of variation of 143.5 percent, potentially reflecting varying degrees of psycho-emotional strain among the personnel. Normalized low-frequency and high-frequency values, with median LFnorm of 0.70 and HFnorm of 0.30 respectively, indicated predominant sympathetic modulation, which is commonly observed as a compensatory mechanism under conditions of elevated stress.These findings highlight the importance of continuous monitoring to evaluate adaptive capacity and inform interventions aimed at maintaining operational readiness in military personnel exposed to prolonged stress during martial law.
Keywords: adaptive potential; military personnel; autonomic nervous system; stress